Utilization of rice husk to enhance calcium oxide-based sorbent prepared from waste cockle shells for cyclic CO2 capture in high-temperature condition - Mohamed, M. (Springer Verlag, 2018)
The CO2 capture capacity and cyclic stability of calcium oxide (CaO) prepared from cockle shells (CS) were enhanced by incorporating rice husk (RH) and binder through wet-mixing method. The cyclic reaction of calcination and carbonation was demonstrated using thermal gravimetric analyzer (TGA) which the calcination was performed in a pure N2 environment at 850 °C for 20 min and carbonation at 650 °C for 30 min in 20 vol of CO2 in N2. The analysis using x-ray fluorescence (XRF) identified silica (Si) as the major elements in the sorbents. The RH-added sorbents also contained several types of metal elements such as which was a key factor to minimize the sintering of the sorbent during the cyclic reaction and contributed to higher CO2 capture capacity. The presence of various morphologies also associated with the improvement of the synthesized sorbents performance. The highest initial CO2 capture capacity was exhibited by CS+10RH sorbent, which was 12 higher than the RH-free sorbent (CS). However, sorbents with the higher RH loading amount such as 40 and 50 wt were preferred to maintain high capture capacity when the sorbents were regenerated and extended to the cyclic reaction. The sorbents also demonstrated the lowest average sorption decay, which suggested the most stable sorbent for cyclic-reaction. Once regenerated, the capture capacity of the RH-added sorbent was further increased by 12 when clay was added into the sorbent. Overall, the metal elements in RH and clay were possibly the key factor that enhances the performance of CaO prepared from CS, particularly for cyclic CO2 capture. Figure not available: see fulltext. © 2018 Springer-Verlag GmbH Germany, part of Springer Nature